A New Clustering Algorithm Using Links' Weight to Decrease Consumed Energy in MANETs - Abbas Afsharfarnia; Abbas Karimi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2014)
One of the most important problems of clustering algorithms in mobile ad-hoc networks (MANETs) is the relatively low stability in generated clusters which are resulted by rapid clusters destruction and high energy consumption in performing the re-clustering processes. Many algorithms have been provided to increase the clusters stability of which the most significant are weight-based algorithms. In weight-based algorithms, only limited information of each node is used to determine its weight and it causes that the best possible option for cluster-head is not selected. The purpose of this paper is providing one weight-based algorithm in which each node's weight determination is performed not only by using its node information but also its neighbor’s nodes information and this work is performed by determining the links' weight between nodes that provide connections between nodes. Via this method, the best possible options can be selected as cluster-head. In simulations and performed experiments, it is revealed that the generated clusters by our proposed algorithms have very high stability.